Prerenal kidney damage in patients with local cold injury - M. M. Mikhailichenko; K. G. Shapovalov; V. A. Mudrov; S. I. Mikhaylichenko; A. V. Mikhaylichenko; Yu. S. Hanina; Yu. V. Mikhailichenko (Acta Biomedica Scientifica, 2022)
Introduction. Important links in the pathogenesis of cold alterations are vascular damage and powerful systemic alterations. The presence of premorbid pathology and the duration of the wound process negatively affects to the function of most organs and systems, including the kidneys. Renal insufficiency in patients with frostbite develops in the acute period of cold damage. This is indicated by a decrease in the amount of urine and an increase in creatinine levels in victims with frostbite. In this regard, the identification and analysis of the dynamics of new markers of renal dysfunction in patients with frostbite is promising both from a scientific and practical point of view.The aim. To investigate the dynamics of changes in serum creatinine, NGAL and cystatin C levels in patients with local cold trauma.Materials and methods. The study included 60 patients with frostbite of the III–IV degree of distal limb segments. The study was carried out depending on the volume of the lesion and the timing from the moment of cryoalteration.The results of the study. In patients with grade III–IV frostbite, an increase in the level of lipocalin and serum creatinine was detected in the blood. The concentration of lipocalin and serum creatinine is directly proportional to the volume of cold-affected tissues. Indicators of lipocalin and serum creatinine decrease in the late stages of cryopreservation. The level of cystatin C significantly decreases during all periods of frostbite; the concentration of the latter does not depend on the severity of cryopreservation.